Nutrient requirements of goats - A review - SARASWAT, B L; SENGAR, O P S (The Indian Journal of Animal Sciences, 2014)
Goats require more DM than that of sheep, cattle and buffaloes, and water requirement is reportedly 4- times of OM consumption by them. The energy and protein requirement is greatly variable depending upon season, size and production. Goats need more minerals specially calcium and phosphorus. They require comparatively higher amount of NaCI also because of salty milk they produce. Goats, generally, consume wide variety of forages. extrinsic supply of vitamins should be ensured for their kids.